Transperitoneal vs extraperitoneal approach for aortic sentinel node detection in endometrial cancerAJOG Global Reports at a Glance - Mikel Gorostidi, MD, MS; Ruben Ruiz, MD; Claudia Galan, MD; Ibon Jaunarena, MD; Paloma Cobas, MD; Arantxa Lekuona, MD; Irene Diez-Itza, MD, PhD (Elsevier, 2022)
BACKGROUND: Although the sentinel lymph node technique in endometrial cancer is currently replacing pelvic and aortic lymphadenectomy for the evaluation of lymph node status in endometrial cancer, its performance is not yet standardized. OBJECTIVE: This study aimed to describe the detection rates and locations of aortic sentinel lymph node detection after dual cervical and fundal indocyanine green injection in patients with endometrial cancer, using the transperitoneal and extraperitoneal approaches. STUDY DESIGN: Between June 26, 2014 and December 31, 2019, 278 patients underwent laparoscopic surgery for endometrial cancer at our institution. In all cases, we performed sentinel lymph node biopsy with dual cervical and fundal indocyanine green injection, and back-up lymphadenectomy in high-risk cases. A post hoc analysis was performed to evaluate differences between the transperitoneal and extraperitoneal approach to aortic sentinel lymph nodes. RESULTS: The detection rates were as follows: overall detection rate: 93.2% (259/278); pelvic detection rate: 90.3% (251/278); bilateral pelvic detection rate: 68.0% (189/278); aortic detection rate: 66.9% (186/278); and isolated aortic detection rate: 2.88% (8/278). Transperitoneal and extraperitoneal aortic detection rates were similar (65.0% and 69.6%, respectively), with no significant differences (P=.441). Isolated aortic metastases were similar in both groups (2% vs 4.7%, respectively; P=.185). The laterality of aortic sentinel lymph node detection was influenced by the surgical approach (P=.002), but not its location above or below the inferior mesenteric artery (P=.166 and P=.556, respectively). CONCLUSION: The detection rates at the aortic level were similar between the transperitoneal and extraperitoneal approaches, with no impact on subsequent pelvic detection. The transperitoneal approach detected more laterocaval, precaval, and interaortocaval nodes, whereas the extraperitoneal approach detected more preaortic and left lateroaortic nodes.